2018
DOI: 10.1002/eco.2056
|View full text |Cite
|
Sign up to set email alerts
|

ENSO and rainfall seasonality affect nutrient exchange in tropical mountain forests

Abstract: Ecohydrological and biogeochemical processes in tropical montane forests canopies are key in the provision of water‐related ecosystem services. However, the sustainability of these services is threatened by environmental change. Climate change in the tropics is suggested to be characterized by an increase in hydrological extremes, with El Niño Southern Oscillations (ENSO) as the main mechanism of climatic variability. For 2 years, we studied the effects of climate variability on a seasonal scale (represented b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
(56 reference statements)
1
1
0
2
Order By: Relevance
“…These conditions affect both nutrient concentrations and their fluxes in water which reach the soil (Van Stan & Pypker, 2015). In the oak forest of the present study, Suescún et al (2019) found that throughfall represented 87% total precipitation, while stemflow represented only 0.4%. In both wet and dry seasons, forest canopies produced nutrient concentration enrichment in throughfall and stemflow.…”
Section: Discussionsupporting
confidence: 48%
“…These conditions affect both nutrient concentrations and their fluxes in water which reach the soil (Van Stan & Pypker, 2015). In the oak forest of the present study, Suescún et al (2019) found that throughfall represented 87% total precipitation, while stemflow represented only 0.4%. In both wet and dry seasons, forest canopies produced nutrient concentration enrichment in throughfall and stemflow.…”
Section: Discussionsupporting
confidence: 48%
“…En términos ecológicos es una región de interés, ya que el uso del suelo se ve determinado por el desarrollo de actividades económicas como la ganadería de leche, que ha desencadenado la siembra de pasto sobre una extensión significativa de su territorio, sumado a los cultivos de papa, tomate de árbol y algunos productos de pancoger (García-Leoz et al, 2018); por otro lado, la intensificación del recurso hídrico para el aprovechamiento de agua en la generación de energía eléctrica, ya que allí se encuentran los embalses de Quebradona, y Río Grande, los cuales proveen agua potable a cerca de dos millones de habitantes en el Valle de Aburrá (Suescún et al, 2018).…”
Section: Zona De Estudiounclassified
“…Por otro lado, con el fin de contar con un registro de la precipitación incidente e interna (esta última es considerada la mayor contribución del flujo de agua que escurre desde las copas de los árboles y alcanza el suelo forestal, y representa entre un 70 y 80 % del total de la precipitación incidente según Suescún et al, 2019), se elaboraron pluviómetros con embudos plásticos de 15 cm de diámetro, conectados por medio de una manguera a un recipiente plástico, que además fue cubierto con una malla fina para impedir que se obstruyera la entrada de agua al recipiente. Para medir la precipitación interna, se instalaron cinco pluviómetros dentro del bosque, cada uno ubicado en el punto central de cada cuadrante "A" de cada uno de los cinco transectos.…”
Section: Instalación De Trampas De Hojarasca Bolsas De Descomposición...unclassified